دراسة الكفاءة الاقتصادية لزراعة التبغ ( فرجينيا – شك البنت ) في محافظة اللاذقية - درويش, نضال; علي, فؤاد (Latakia University Journal -Biological Sciences Series, 2019)
نظراً للأهمية الاقتصادية الكبيرة لمحصول التبغ في سورية, والذي يعد من أهم المحاصيل الزراعية الاستراتيجية التي تساهم في رفع مستوى الحياة الاجتماعية, و زيادة معدل النمو الاقتصادي, ركزنا في هذا البحث على المزايا الاقتصادية, والعوائد المادية الناتجة عن زراعة التبغ (فرجينيا-شك البنت) في محافظة اللاذقية, من خلال دراسة التكاليف الإنتاجية, ومؤشرات الكفاءة الاقتصادية بالاستناد إلى بيانات ومعطيات تم جمعها من موقعي البحث (درغامو-الدالية), معتمدين في تحديد كلفة المواد والأجور أسعار السوق السائدة, وقد سعينا في هذا البحث لتحقيق الأهداف الآتية : 1- دراسة واقع وآفاق تطور زراعة التبغ في سورية بصفة عامة واللاذقية بصورة خاصة. 2- دراسة وتحليل التكاليف الإنتاجية لتبغ الفرجينيا وشك البنت. 3- إجراء التقويم الاقتصادي لكفاءة زراعتهما في محافظة اللاذقية. وبنتيجة الدراسة توصلنا إلى النتائج الآتية : 1- يعادل صافي الربح السنوي المحقق في الدونم الواحد من الفرجينيا( 10518.7 ) ليرة سورية, ومن شك البنت( 7795.8 ) ل.س. 2- بلغ معامل الربحية بالقياس إلى رأس المال المستثمر من الفرجينيا( 1.98% ), ومن شك البنت(2.44%), وبلغ بالقياس إلى تكاليف الإنتاج من الفرجينيا(49.10% ), ومن شك البنت(54.28 % ). 3- بلغ مؤشر فترة استرداد رأس المال لتبغ الفرجينيا( 2.03 ), ولشك البنت( 1.84 ), ويعد هذا المؤشر جيداً. Tobacco is one of the major strategic crops produced in Syria. It has great economic importance, contributes to the improvement of social life level, and increases the economic growing average.In this study, we focused on the economic properties and the finance returns of tobacco cultivation (Virginia-Shak Elbent) in Lattakia province by examining production costs and economic efficiency indexes, according to the information presented from the location of study (Derghamo-Aldalie) and depending on the recent prices of market. Thus, this study aimed i) to observe tobacco cultivation development, generally in Syria and specifically in Lattakia, ii) to analyze the production cost of Virginia and Shak Elbent cultivars, and iii) to achieve the economic evaluation of their cultivation efficiency in Lattakia province. The study revealed that 1) the annual net profit of 0.1 ha for Virginia and Shak Elbent cultivars was 10518.7 and 7795,8 SP respectively, 2) the profitability rate compared to capital for Virginia and Shak Elbent cultivars recorded 1.98 % and 2.44 %; meanwhile, it constituted 49.1 % and 54.28 % in comparison to production cost, and 3) capital resuming time index values were 2.03 for Virginia, and 1.84 for Shak Elbent, which are considered good ones.